Revision Total Hip Replacement: A Case Report - Rahman, Md Hafizur; Sarker, Md Mohoshin; Matin, Md Abdul (Delta Medical College Journal, 2013)
Total hip replacement is a reconstructive procedure that has improved the management of those diseases of the hip joint that have responded poorly to conventional medical therapy. Conventional, primary total hip replacement is a durable operation in the majority of patients. A hip replacement is a mechanical device with parts that are assembled before and during the operation. But the possible complications of total hip arthroplasty, and its clinical performance over time, is a challenging occasion to the surgeons, and such a challenge we faced with our presenting patient. A 68 year old lady with history of cemented bipolar hemiarthroplasty done in a tertiary care hospital, due to fracture neck of the left femur having the history of diabetes, chronic kidney disease, heart disease, anaemia, and mental disorders presented with loosened prosthesis, thinning of medial proximal cortex of the femur which had broken within few months after surgery. She complained of painful walking at left hip joint. There was also evidence of chronic infective and degenerative arthritis of acetabular component of the affected hip joint. Cemented revision total hip replacement surgery was performed with expert multidisciplinary involvement. On 2nd postoperative day the patient was allowed to walk on operated limb with the aid of walker. On 12th postoperative day all the stitches were removed and wound was found healthy. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15920 Delta Med Col J. Jul 2013;1(2):58-61